PENGARUH LEVERAGE, PROFITABILITAS, TATA KELOLA DAN KARAKTERISTIK PERUSAHAAN PADA PERATAAN LABA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2013-2015 - Orisa Paramiga Ladistra; Sofie Sofie (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
The purpose of This study was to analyze the effect of Financial Leverage, Profitability, Governance and Characteristics of the company on income smoothing. Analyze these things in a company should be done because it will be very important and will greatly affect the financial infranstructure and corporate governance it self. Therefore this study is very important, once carried out as a performance assessment of the company concered. The Sampel for this sudy we used data from the 52 companies listed in Indonesia Stock Exchange period 2013 until 2015. This research uses secondary data from the companies that we make samples for this study. In this study, the sampling is the purposive sampling method. The analysis for the hypothesis in thisstudy is multiple regression analysis with the software SPSS 20. The results of this study indicate that the variable Financial Leverage and Profitability have significant influence on income smoothing. Variable governance in the proxy to the board of directors, audit committees, institutional ownership doesn’t have significant effect on income smoothing. Variable characteristics doesn’t have significant effect on income smoothing.